Survival-Weighted Health Profiles in Nasopharyngeal Cancer Patients - Lai, Chia-Hsuan; Chen, Wen-Cheng; Fang, Chiung-Cheng; Chen, Miao-Fen (Frontiers in Oncology, 2021)
Introduction In treating nasopharyngeal cancer (NPC) patients, excellent tumor control and patient survival rates can be achieved in the era of intensity-modulated radiotherapy (IMRT). However, treatment-related toxicities affect the quality of life (QoL) of NPC survivors. This study was designed to estimate the life expectancy (LE), quality-adjusted life expectancy (QALE) and survival-weight psychometric scores (SWPS) in NPC patients. Methods A sample of 875 non-metastatic NPC patients diagnosed between January 1, 2009 and June 30, 2013 was collected for estimation of lifetime survival function. All patients were followed up until death or censored on December 31, 2015. To obtain the utility and psychometric score for estimation of LE, QALE and SWPS, 99 patients were measured with the Taiwanese version of the EuroQol instrument (EQ-5D) and the Taiwan Chinese versions of the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ)-C30 and QLQ-H&N35 between October 1, 2013 and December 31, 2017. The LE of NPC patients was obtained using linear extrapolation of a logit-transformed curve and was adjusted by the corresponding QOL function to calculate the QALE and SWPS. Results The mean age of the 875 non-metastatic NPC patients was 50.3 years. The average LE and QALE were estimated to be 15.5 years and 14.3 quality-adjusted life years (QALYs) for NPC patients and 29.5 years and 29.5 QALYs for the reference population, respectively. On average, the lifelong duration of pain and painkiller use were 6.0 years and 2.2 years. The lifelong duration of impairment of swallowing, speech, smell and taste were 14.0 years, 9.8 years, 8.7 years and 7.5 years, respectively. The life long duration of problems with dry mouth, teeth, emotion, fatigue, sleep and social contact were 13.4 years, 10.1 years, 9.1 years, 12.3 years, 6.7 years, and 4.5 years, respectively. The lifelong duration of tube-feeding was 1.3 months. Conclusions NPC patients had an estimated LE of 15.5 years and QALE of 14.3 QALYs. Furthermore, SWPS could help people understand more about the impact of radiotherapy on NPC patients. These data could also be useful for policy makers to allocate limited resources in health care.